2021
DOI: 10.6000/2371-1655.2021.07.01
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Citizenship Education Framework in Social Studies Teachers’ Education Programme in Sultanate of Oman

Abstract: Educational system in Oman is attempting to educate Omani students to be "good" citizens in an increasingly globalized society. However, a few studies that have been conducted until now in Oman revealed a gap between the intentions of the educational policy of teaching citizenship education in the schools and the actual practices of teacher education preparation programs. Therefore, any endeavor to develop citizenship in Oman schools will not achieve its goals without taking teacher education into account both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Several previous studies have explored the fulfillment of GCED requirements in the Oman context based on policy and literature analysis. A study conducted by Al-Maamari [27] on GCED in a social studies primary teacher preparation program showed that both teachers and students have suffered from limited and traditional applications of GCED in the social studies preparation program. This finding was linked to the dissatisfaction of policymakers, especially the MOE, with the insufficient preparation of teachers for the development of citizenship.…”
Section: Oman Gced Experience and Its Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have explored the fulfillment of GCED requirements in the Oman context based on policy and literature analysis. A study conducted by Al-Maamari [27] on GCED in a social studies primary teacher preparation program showed that both teachers and students have suffered from limited and traditional applications of GCED in the social studies preparation program. This finding was linked to the dissatisfaction of policymakers, especially the MOE, with the insufficient preparation of teachers for the development of citizenship.…”
Section: Oman Gced Experience and Its Challengesmentioning
confidence: 99%
“…Similarly, some studies conducted in Oman have shown that GCED is still associated with the field of social studies [9,25,27]. Therefore, the role of other subjects such as English, geography, science, and Islamic culture must be strengthened in order increase the effectiveness of GCED.…”
Section: Oman Gced Experience and Its Challengesmentioning
confidence: 99%
See 1 more Smart Citation